Translation: a new paradigm (translation. a transdisciplinary journal, 2022)
Today, translation scholarship and practice face a twofold situation. On the one hand translation studies is enjoying unprecedented success: translation has become a fecund and frequent metaphor for our contemporary intercultural world, and scholars from many disciplines, for instance, linguistics, comparative literature, cultural studies, anthropology, psychology, communication and social behavior, and global studies have begun investigating translational phenomena.